Hubungan Pengetahuan dengan Tingkat Kepatuhan Membaca Label Pangan Makanan Kemasan pada Mahasiswa Prodi Gizi Universitas Sulawesi Barat - Umi Kalsum Yusuf; Wahdaniyah; Ummu Kalsum (Nutrition Science and Health Research, 2024)
The act of reading food labels is one of the pillars of the Balanced Nutrition Message (BNM) which can support a healthy lifestyle by helping consumers choose the food they consume to casure if is safe for their health. This research aims to determine the relationship between knowledge and the level of compliance with reading food labels for packaged foods among students of the Nutrition Study Program at the University of West Sulawesi. This research uses an observational type of research using a cross sectional design with a population of 380 nutrition study program students. The sample used was 87 nutrition study program students taken using the Probability Sampling technique. Data collection used a questionnaire by using google from and statistical data analysis used the chi-square test. The results of statistical tests show that respondents' knowledge of food labels in the good category (4.6%), in the sufficient category (69.0%) and in the poor category (26.4%). Meanwhile, for the level of compliance, respondents who had the highest level of compliance were in the medium category (85.1%), in the high category (11.5%), and in the low category (3.4%). The data in this study shows that the respondents' knowledge regarding food labels is in the sufficient category and the level of compliance in reading food labels is in the medium category. The conclusion of this study shows that the ρ value ≤ α (0.05), which means there is a relationship between Knowledge and the Level of Compliance with Reading Food Labels for Packaged Foods among Nutrition Study Program Students at West Sulawesi University. Nutrition students are expected to be able to educate the public about the importance of reading food labels on packaged foods before buying certain products, because they can have negative impacts.